Design of Terahertz Antenna Based on fractal distribution of graphene layers - حسن, رنا; السموءل صالح; تغريد حداد (Latakia University Journal -Engineering Sciences Series, 2023)
In last few decades ,Microstrip antenna plays an important role in the field of wireless communications and fields of biomedical and military applications, due to its compact size, light weight and better ease of fabrication. Among many materials, graphene is attracting many researchers in developing Microstrip -antenna due to its unique electrical properties .In This work, we propose a design of terahertz antenna based on Cantor distribution of graphene, that provides a multi-dimensional structure, in order to generate different frequencies. The requested antenna was designed using CST simulator and analyzed the effect of the variation of resonance patch numbers and dimensions on the antenna proprieties. The proposed antenna has agood gain and return loss at terahertz frequencies.